Development of a UDL-Based Learning Management System by Including the Voice of Deaf and Autistic Students - Irine Kurniastuti; Antonius Ian Bayu Setiawan; Silverio Raden Lilik Aji Sampurno; Andhana Prakosajaya (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Learning management system is one of the learning spaces that can be used flexibly and independently in inclusive classes. This study described the steps in developing Semester Learning Plan (SLP) and LMS through 5 stages of design thinking: Empathize, Define, Ideate, Prototype, and Test. This study involved 3 deaf students, 1 autistic student, and 29 non-disabled students as respondents and experts to assess and provide input on the development of SLP and LMS. The results of the LMS development showed an increase in students' assessment of LMS accessibility with a moderate positive effect. The LMS was categorized as good in terms of its fulfilment of UDL principles, accessibility of learning tools, pedagogical feasibility, and ease of use. Further improvements are needed to advance the accessibility of the LMS.